Electronic adherence monitoring device performance and patient acceptability: a randomized control trial. (4th May 2017) - Chan, Amy Hai Yan; Stewart, Alistair William; Harrison, Jeff; Black, Peter Nigel; Mitchell, Edwin Arthur; Foster, Juliet Michelle
ABSTRACT: Background : To investigate the performance and patient acceptability of an inhaler electronic monitoring device in a real-world childhood asthma population. Methods : Children 6 to 15 years presenting with asthma to the hospital emergency department and prescribed inhaled corticosteroids were included. Participants were randomized to receive a device with reminder features enabled or disabled for use with their preventer. Device quality control tests were conducted. Questionnaires on device acceptability, utility and ergonomics were completed at six months. Results : A total of 1306 quality control tests were conducted; 84% passed pre-issue and 87% return testing. The most common failure reason was actuation under-recording. Acceptability scores were high, with higher scores in the reminder than non-reminder group (median, 5 th -95 th percentile: 4.1, 3.1–5.0 versus 3.7, 2.3–4.8; p < 0.001). Most (>90%) rated the device easy to use. Feedback was positive across five themes: device acceptability, ringtone acceptability, suggestions for improvement, effect on medication use, and effect on asthma control. Conclusions : This study investigates electronic monitoring device performance and acceptability in children using quantitative and qualitative measures. Results indicate satisfactory reliability, although failure rates of 13–16% indicate the importance of quality control. Favorable acceptability ratings support the use of these devices in children.